2014
DOI: 10.4103/1673-5374.131602
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic thyroid hormone, levothyroxine, protects cholinergic neurons in the hippocampus of naturally aged mice

Abstract: The thyroid hormones, triiodothyronine and thyroxine, play important roles in cognitive function during the mammalian lifespan. However, thyroid hormones have not yet been used as a therapeutic agent for normal age-related cognitive deficits. In this study, CD-1 mice (aged 24 months) were intraperitoneally injected with levothyroxine (L-T4; 1.6 μg/kg per day) for 3 consecutive months. Our findings revealed a significant improvement in hippocampal cytoskeletal rearrangement of actin and an increase in serum hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
(72 reference statements)
2
12
0
Order By: Relevance
“…Such correlation has also been observed in aged rodents (Fu et al, 2014; Lim et al, 2015). The first clinical approach has thus consisted in inhibiting the decrease of acetylcholine (ACh) by blocking its degradation by acetylcholinesterase (AChE) in the synaptic cleft (Marighetto et al, 2008).…”
Section: Introductionsupporting
confidence: 64%
“…Such correlation has also been observed in aged rodents (Fu et al, 2014; Lim et al, 2015). The first clinical approach has thus consisted in inhibiting the decrease of acetylcholine (ACh) by blocking its degradation by acetylcholinesterase (AChE) in the synaptic cleft (Marighetto et al, 2008).…”
Section: Introductionsupporting
confidence: 64%
“…Returning to the rodent models, Fu et al showed that the administration of L-T 4 to aged mice can significantly improve their learning and memory capacities, through increases of both serum and 16 brain concentrations of free T 3 and T 4 (Fu et al, 2014). Similar treatments also can counteract depression in rats and humans (Bauer et al, 2005;Ge et al, 2016;Uhl et al, 2014).…”
Section: Roles Of Th In the Ageing Brainmentioning
confidence: 99%
“…Pharmalogical inhibition of actin polymerization within the hippocampus impairs object placement memory formation in female rats in a dose-dependent fashion (Nelson et al, 2012 ). Further, interventions that induce actin rearrangement improve MWM performance in mice (Fu et al, 2014 ) without increasing total actin, confirming actin-induced activity-dependent synaptic remodeling in a manner independent of protein synthesis. Enlargement of the actin cytoskeleton and subsequent stabilization, however, may be considered a critical determinant of memory consolidation (Rudy, 2015 ).…”
Section: Discussionmentioning
confidence: 84%